Crossing the human threshold
1 online resource
Keywords: "When was the human threshold crossed? What is the evidence for evolving humans and their emerging humanity? This volume explores in a global overview the archaeology of the Middle Pleistocene, 800,000 to 130,000 years ago when evidence for innovative cultural behaviour appeared. The evidence shows that the threshold was crossed slowly, by a variety of human ancestors, and was not confined to one part of the Old World. Crossing the Human Threshold examines the changing evidence during this period for the use of place, landscape and technology. It focuses on the emergence of persistent places, and associated developments in tool use, hunting strategies and the control of fire, represented across the Old World by deeply stratified cave sites. These include the most important sites for the archaeology of human origins in the Levant, South Africa, Asia and Europe, presented here as evidence for innovation in landscape-thinking during the Middle Pleistocene. The volume also examines persistence at open locales through a cutting-edge review of the archaeology of Northern France and England.Crossing the Human Threshold is for the worldwide community of students and researchers studying early hominins and human evolution. It presents new archaeological data. It frames the evidence within current debates to understand the differences and similarities between ourselves and our ancient ancestors. "--Provided by publisher.